Mimetic Desire and Child Violence in Merindu Baginda Nabi: A Girardian Perspective - Jafar Lantowa; Sudibyo Sudibyo; Novi Siti Kussuji Indrastuti (KEMBARA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2025)
Child violence often arises as a consequence of uncontrolled academic rivalry, driven by mimetic desire. This study aims to analyse the depiction of child violence in Merindu Baginda Nabi by Habiburrahman El Shirazy through the lens of René Girard’s theory of mimetic desire. Employing a qualitative research methodology with a descriptive-interpretative approach, this study examines words, phrases, and excerpts from the novel that represent child violence. Data collection was conducted through library research, while content analysis was carried out using data reduction, data presentation, and conclusion-drawing techniques. The findings of this study reveal that child violence in Merindu Baginda Nabi by Habiburrahman El Shirazy stems from mimetic desire, with the character Rifa positioned as the subject and Arum as the mediator. This dynamic escalates into rivalry and ultimately results in violence. However, the narrative demonstrates that such violence can be resolved through reconciliation and self-reflection. Accordingly, this study contributes to a deeper understanding of child violence in educational settings by applying literary analysis through Girard’s mimetic theory. The use of Girardian theory offers a novel perspective on the root causes of child violence in education. It contributes significantly to literary criticism and the broader discourse on conflict resolution through literature.